The performance of the Small East African goats and their Saanen crosses in Malawi - Karua, S.K.; Banda, J.W. (1994)
The performance of randomly selected Malawian local goats and their Saanen crosses was compared. The average litter size at kidding was 1.35 and 1.52, respectively. Birth weights, 12-week weights and weaning weights at 17 weeks were respectively 2.2 kg (SE = 0.12 kg), 8.2 kg (SE=0.41 kg) and 10.7 kg (SE = 0.62 kg) for the local goats and 2.31 kg (SE=0.40 kg), 11.4 kg (SE = 1.59 kg) and 19.2 kg (SE = 2.39 kg) for the Saanen crosses (P<0.001). The growth rate up to weaning was 71 g (SE = 4.8 g/day) and 139 g (SE=18.5 g/day) for the local goats and their Saanen crosses respectively (P<0.01). Saanen crosses produced more milk (83 kg, SE 4 kg) during a 12-week period (P<0.001) than the local does (37 kg, SE 5 kg).The results indicate that crossing Small East African goats with Saanens would improve not only milk production, but also the growth rate of their kids, contributing to improved meat production.